Osteoid Osteoma of Distal Phalanx of Little Finger - Joshi, Amit; Kayastha, Nirab (Medical Journal of Shree Birendra Hospital, 2013)
Osteoid Osteoma is benign bone forming tumor commonly occurs in lower limbs. Osteoid Osteoma of upper limb is rare, and it is extremely rare in hands. We report a case of a 20 year old male who presented with complaints of pain in nail bed of left little finger over a period of one year with gradually increasing swelling and deformity of nail. Radiological examination revealed a well-defined lytic lesion with sclerotic margin at distal phalanx with a nidus at center. Curettage and removal of nidus was done under digital nerve block. He was symptom free from next day of surgery and the tip of the finger has significantly regained its original shape over a period of two years. The aim of this paper is to report yet another uncommon case of osteoid Osteoma located at distal phalanx of little finger. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/46-49 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7911